2014
DOI: 10.1179/1351000214y.0000000096
|View full text |Cite
|
Sign up to set email alerts
|

Cissus quadrangularisextract attenuates hyperglycaemia-mediated oxidative stress in streptozotocin-induced diabetic rats

Abstract: This study suggests an anti-diabetic potential of CQSF, mediated through the modulation of the antioxidant defence system. The ethyl acetate fraction of Cissus quadrangularis is rich in quercetin and this indicates that the supplementation of CQSF might be beneficial as a food supplement for the attenuation of diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…For bone fractures and obesity/overweight management, this is the first meta-analysis summarizing the clinical benefits of Cissus for these indications. However, benefits of Cissus for these indications and other bone and joint diseases were demonstrated in several preclinical studies (Panthong et al 2007, Sharma and Patni 2007, Sharp et al 2007, Jiji et al 2009, Chidambaram and Carani 2010, Chaudhari et al 2013, Lekshmi et al 2014. The proposed mechanisms of Cissus extract for bone and joint diseases are enhancing bone growth and healing, analgesic, antiinflammatory, and anti-osteoporotic activities (Panthong et al 2007, Sharma and Patni 2007, Potu et al 2010, AbdJalil et al 2012, Aswar et al 2012, Banu et al 2012, Gupta et al 2012, Sirasanagandla et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bone fractures and obesity/overweight management, this is the first meta-analysis summarizing the clinical benefits of Cissus for these indications. However, benefits of Cissus for these indications and other bone and joint diseases were demonstrated in several preclinical studies (Panthong et al 2007, Sharma and Patni 2007, Sharp et al 2007, Jiji et al 2009, Chidambaram and Carani 2010, Chaudhari et al 2013, Lekshmi et al 2014. The proposed mechanisms of Cissus extract for bone and joint diseases are enhancing bone growth and healing, analgesic, antiinflammatory, and anti-osteoporotic activities (Panthong et al 2007, Sharma and Patni 2007, Potu et al 2010, AbdJalil et al 2012, Aswar et al 2012, Banu et al 2012, Gupta et al 2012, Sirasanagandla et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms of Cissus extract for bone and joint diseases are enhancing bone growth and healing, analgesic, antiinflammatory, and anti-osteoporotic activities (Panthong et al 2007, Sharma and Patni 2007, Potu et al 2010, AbdJalil et al 2012, Aswar et al 2012, Banu et al 2012, Gupta et al 2012, Sirasanagandla et al 2014. Whereas, inhibition of certain enzymes as alpha amylase, glucosidase and lipase, anti-hyperglycemic, anti-lipidemic activities, and tissue protective effects associated with fatty lipid and carbohydrate metabolism are the mechanisms for obesity/overweight management (Sharp et al 2007, Jiji et al 2009, Chidambaram and Carani 2010, Chaudhari et al 2013, Lekshmi et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…CQ powder has also been clinically evaluated to reduce the intermaxillary fixation time for patients with fracture of the mandible . Moreover, phytocomponents present in CQ extracts have demonstrated multifunctional biological effects such as antioxidant capacity, analgesia, being anti‐inflammatory, inducing apoptosis in cancer cells yet causing liver dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Lekshmi, et al [17,18] suggested the anti-diabetic potential of C. quadrangularis stem extract, mediated through the modulation of the antioxidant defence system. The ethyl acetate fraction is rich in quercetin supplementation of the plant might be bene icial as a food supplement for the attenuation of diabetic complications.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%